Synthesis, characterization and in vitro anticancer activity of Novel 8,4’ : oxyneolignan analogues - Souza, Gisele C. (2017)
Neolignans are a class of natural products with a wide range of biological effects. These substances are of great synthetic and biological interest, especially in searching for novel anticancer agents. In this paper, we report the synthesis of a new subclass of 8,4’-oxyneolignan analogues (β-ketoethers and β-ketoesters) and their cell viability assay on twenty four different cancer cells, among leukemias and carcinomas. Three compounds inhibited the growth of most human cancer cells. 2-Oxo-2-phenylethyl(2E)-3-[4-(2-oxo-2-phenylethoxy) phenyl]prop-2-enoate showed an antiproliferative activity superior to doxorubicin for U-87, U-138 MG and H1299 cell types and (E)-2-oxo-2-phenylethyl 3-(3-methoxy-4-(2-oxo-2-phenylethoxy)phenyl)acrylate was found to be very selective, demonstrating a growth inhibition of 92.0% against KG-1 cells. Furthermore, 1-oxo-1-phenylpropan-2-yl cinnamate exhibited significant inhibition activity in a range of 52.2 to 91.2% against twelve kinds of leukemia cell lines, revealing excellent results and very comparable to the reference drug.